The effects of credit supply shocks on Malaysia's economy - Khair Afham, M. S. M.; Rosland, Anitha (University Putra Malaysia, 2022)
This study has examined the impacts of credit supply shocks and other common economic shocks (aggregate demand & supply and monetary shocks) on Malaysia's macroeconomic variables, using the Bayesian structural vector autoregressive (SVAR) model and employing sign restrictions. The results showed that an expansionary credit supply shock positively affected the Malaysian economy, consistent with the existing literature. Based on the variance decomposition finding, credit supply shocks explained a significant portion of the anticipated variation in the GDP growth, inflation, and, most importantly, credit growth in Malaysia. This study further decomposed total private non-financial corporate loans into two components: households and non-financial firms. Unlike other economies that have extensively researched this subject matter (US, UK, Euro Area), the growth rate of households and non-financial firms differed greatly in Malaysia. The empirical findings revealed considerable distinctions between these two components, indicating that different treatments or policy formulations are required rather than employing the same policy to boost or govern Malaysia's credit market.